2014
DOI: 10.1007/s11625-014-0277-1
|View full text |Cite
|
Sign up to set email alerts
|

Embodying Tao in the ‘Restorative University’

Abstract: This paper proposes a new generative metaphor, the 'Restorative University' which embodies an associated Taoist human-nature narrative. It aims to counter what is contextualised here as the bio-cultural disconnection of universities despite their espoused commitment to sustainability. This conceptual research draws on multiple disciplines such as environmental psychology alongside Taoist philosophy to open up a reflexive dialogue between multiple organizational actors. Moreover, in order to understand the pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 78 publications
0
1
0
Order By: Relevance
“…In different people and in different areas of activity in an organization and in different environments, compensation involves different proportions of Yin and Yang (Lin et al, 2013). Jones (2015) indicated that one of the characteristics of Taoist organizational behavior was reflect a cultural preoccupation with balance and the quest for optimal harmony with the natural order that presents such humility. Asquith & Kalland (1997) Waistell, 2012).…”
Section: Taoist Behavior In the Organizationmentioning
confidence: 99%
“…In different people and in different areas of activity in an organization and in different environments, compensation involves different proportions of Yin and Yang (Lin et al, 2013). Jones (2015) indicated that one of the characteristics of Taoist organizational behavior was reflect a cultural preoccupation with balance and the quest for optimal harmony with the natural order that presents such humility. Asquith & Kalland (1997) Waistell, 2012).…”
Section: Taoist Behavior In the Organizationmentioning
confidence: 99%